Abraham Fraunce : the shepherds' logic and other dialectical writings - Fraunce, Abraham, active 1587-1633 (Modern Humanities Res Ass, 2016)
Abraham Fraunce’s The Shepherds’ Logic (c. 1585) is one of the first English adaptations of Petrus Ramus’s Dialecticae libri duo (1556). Preserved in a manuscript also containing two shorter essays on Ramist dialectic, the work was later modified and enlarged for publication as The Lawyers’ Logic (1588). But Fraunce’s substantial and almost exclusive use of Edmund Spenser’s The Shepherds’ Calendar (1579) as the source for practical examples makes the manuscript treatise a unique document revealing the influence of the Ramist reform of the arts of discourse on the new literary elite led by Philip Sidney and Gabriel Harvey. This is the first published critical edition of Fraunce’s early treatise and the two companion essays. It presents the texts in modernized spelling, traces their sources and contexts, and draws out their literary and philosophical implications. It also includes relevant excerpts from The Lawyers’ Logic, such as Fraunce’s quantitative-verse translation of Virgil’s Second Eclogue and its Ramist analysis, and a full catalogue of the quotations from Spenser’s Calendar. As a whole, this edition sees Fraunce’s pastoral logic as a first-hand testimony showing how scholarly training in the Renaissance arts of discourse enlightened the composition and interpretation of poetic texts.